Menciptakan Ruang Gerak yang Bebas dari Ancaman Kekerasan - Baiq Dewi Kamariani; Nur Fitri Eka Asbarini; Abdul Chalel Ramham; Salmi Yuniar Bahri; Hartiani Hartiani (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This service was carried out in Perian Village involving several elements consisting of the local community, regional office, village government and KKN participants. The aim of this service is that it is hoped that participants can understand the factors that cause sexual violence and can avoid it, thereby creating a space for movement that is safe and free from the threat of violence. The methods used in this service are the lecture method, FDG and two-way discussion between resource persons and participants. Whatever the results of this service, Perian Village is still classified as vulnerable to sexual violence, therefore it is hoped that the local community will be more alert and the relevant government should pay attention to the risks for perpetrators as early as possible through the formation of regulations and sanctions for perpetrators and intense guidance for victims so that victims not disturbed by his psychology.